Optical performance and radiation stability of polymer X‐ray refractive nano‐lenses. (1st April 2019) - Barannikov, Alexander; Polikarpov, Maxim; Ershov, Petr; Bessonov, Vladimir; Abrashitova, Ksenia; Snigireva, Irina; Yunkin, Vyacheslav; Bourenkov, Gleb; Schneider, Thomas; Fedyanin, Andrey A.; Snigirev, Anatoly
Abstract : Full‐field X‐ray microscopy with a resolution of 100 nm, achieved by polymer compound 3D refractive nano‐lenses, is demonstrated. This article also dicusses issues related to lens aberrations, astigmatism and radiation stability, and thus ways of improving the lens further are considered. Abstract : Full‐field X‐ray imaging and microscopy with polymer compound refractive nano‐lenses is demonstrated. Experiments were carried out at beamline ID13 at the European Synchrotron and yielded a resolution of 100 nm. The lenses were demonstrated to be functioning even after an absorbed dose of ∼10 7  Gy. This article also discusses issues related to lens aberrations, astigmatism and radiation stability, and thus ways of improving the lens further are considered. Polymer nano‐lenses are versatile and are promissing for nano‐focusing and compact X‐ray microscopy.